Vermicomposted tannery wastes in the organic cultivation of sweet pepper: growth, nutritive value and production - Ramom Rachide Nunes; Lívia Botacini Favoretto Pigatin; Ticiane Silva Oliveira; Rhaissa Mecca Bontempi; Maria Olímpia Oliveira Rezende (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose In this study, vermicomposted tannery wastes were applied in the organic cultivation of sweet pepper in a greenhouse. The effects of this organic matter addition on plant development and on the distributions of Cr(III) and Cr(VI) in plant tissues and organs were assessed. Methods In a greenhouse, organic sweet peppers were cultivated adding vermicomposted tannery to the substrate (sample VRC) and the results were compared with the samples control (dYL; only soil) and reference (NPK; adding mineral fertilizer). The growth, nutritive value and fruit production were assessed to evaluate the plant development in different types of substrate. Besides evaluating the biostimulant effect of vermicomposts, the distributions of Cr in plant tissues were also studied. Results Up to three harvested sweet peppers were obtained per plant, compared with only one fruit for the reference treatment with NPK addition. Based on the Cr dynamics in the plants, the highest concentration was found in the fruits, varied as follows: fruits > stem and stalks > leaves = root; however, the Cr concentration in the fruits was statistically the same across all treatments. Additionally, only Cr(III) was detected and quantified in the fruits. Conclusion The addition of vermicompost was biostimulating to plants and positively influenced their development. Based on the Cr dynamics in the plants, since the Cr concentration was the same across all treatments, it demonstrated that the addition of tannery residues to the vermicompost did not negatively influence the health benefits or food security of the produced fruits.